Early loss of cerebellar Purkinje cells in human and a transgenic mouse model of Alzheimer's disease. (3rd July 2021) - Chaudhari, Kiran; Wang, Linshu; Kruse, Jonas; Winters, Ali; Sumien, Nathalie; Shetty, Ritu; Prah, Jude; Liu, Ran; Shi, Jiong; Forster, Michael; Yang, Shao-Hua
ABSTRACT: Background: The cerebellum's involvement in AD has been under-appreciated by historically labeling as a normal control in AD research. Methods: We determined the involvement of the cerebellum in AD progression. Postmortem human and APPswe/PSEN1dE9 mice cerebellums were used to assess the cerebellar Purkinje cells (PC) by immunohistochemistry. The locomotor and spatial cognitive functions were assessed in 4- to 5-month-old APPswe/PSEN1dE9 mice. Aβ plaque and APP processing were determined in APPswe/PSEN1dE9 mice at different age groups by immunohistochemistry and Western blot. Results: We observed loss of cerebellar PC in mild cognitive impairment and AD patients compared with cognitively normal controls. A strong trend towards PC loss was found in AD mice as early as 5 months. Impairment of balance beam and rotorod performance, but no spatial learning and memory dysfunction was observed in AD mice at 4–5 months. Aβ plaque in the cerebral cortex was evidenced in AD mice at 2 months and dramatically increased at 6 months. Less and smaller Aβ plaques were observed in the cerebellum than in the cerebrum of AD mice. Similar intracellular APP staining was observed in the cerebellum and cerebrum of AD mice at 2 to 10 months. Similar expression of full-length APP and C-terminal fragments were indicated in the cerebrum and cerebellum of AD mice during aging. Discussion: Our study in post-mortem human brains and transgenic AD mice provided neuropathological and functional evidence that cerebellar dysfunction may occur at the early stage of AD and likely independent of Aβ plaque.